Daughters of Africa and the Gender Politics of Urban Segregation in Durban, 1935-1937 - du Toit, Marijke (The Journal of Natal and Zulu history, 2021)
In 1935 the Durban Town Council announced a policy that would require all 'Native women' to apply for permission to come to town as part of a system of compulsory registration, which also required proof of legitimate residency for those African women who already lived within municipal boundaries. This article considers how organised African women from the local kholwa (mission-educated Christian) elite asserted themselves as participants in the public sphere of local government. Tensions about the new plans to enforce a system of passes for African women came to a head in 1937 when police conducted raids on homes in the city. In their response, African women's welfare societies organised as part of Daughters of Africa pushed the boundaries of the politics of petitioning through vocal and public protest. I consider the gendered politics of urban segregation through the prism of official, municipal documentation; through reportage in the public forum that constituted Ilanga lase Natal - a newspaper still dominated by men who often expressed ambivalence about 'their' women's presence in town - and also through life history interviews conducted many years later with a key organiser of the protests, Bertha Mkhize.